Leuit and the Food Preservation System During the Pandemic as a Form of Local Wisdom of the Indigenous People of Kasepuhan Sinar Resmi Cisolok Sukabumi West Java - Firmansyah, Eka Kurnia; Sunarni, Nani; Maulia, Lia (Pattimura University, 2022)
This research discusses the system of food storage during the pandemic through rice storage in Leuit in the community of Kasepuhan Sinar Resmi Village, Cisolok District, Sukabumi Regency, also examines what tools, times and types are used to carry out the belief rituals they use in food storage, especially during the Seren Taun traditional ceremony. This research discusses how the food storage system during the pandemic through rice storage in Leuit in the community of Kasepuhan Sinar Resmi Village, Cisolok District, Sukabumi Regency, also examines what tools, times and types are used to carry out the belief rituals they use in food storage, especially during the Seren Taun traditional ceremony. The results of this research can be described as a stable food storage system for hundreds of years, namely from the time of the ancestors until now and it was found what moral values are contained in the implementation of religious rituals or beliefs that they believe in. Another benefit of this research is that the community and local governments are expected to be able to provide information input and become one of the reference discourses in the food preservation system and the preservation of the inventory of cultural heritage of the community, especially the Sundanese in the southern West Java region